Avaliação da condição de vida dos alunos e de suas famílias durante a Covid-19 e possíveis impactos e seus resultados - RÊGO, Jully Kelly Moraes (2022)
This article presents a study on the impacts of the COVID-19 pandemic on the socioeconomic life of students and their families and the influence that such realities will result in the learning of undergraduate students at the Federal University of Pará UFPA, Abaetetuba campus, which made it possible to question the government measures that are contemplating students and their families in this pandemic scenario. For the construction of this work, the methodology adopted was the bibliographic research of a quantitative-qualitative nature, and forms made available electronically, with the objective of understanding the reality of university students and their families during the chaotic period of covid-19. Thus, the data that support this investigation were collected from scientific articles published online, journals and books. The results found show that public policies cover less and less students and their families, due to the dismantling of Federal Universities provided by the Ministry of Education and the external influences arising from the capitalist system, ending up directly affecting students in teaching and learning by lack of resources and access materials, leaving them with demotivation and finally, in the worst case, evasion, since in most cases there are no means that can guarantee the continuity of the student within the university.